การศึกษาเชิงวิเคราะห์นวนิยายเรื่องสิทธารถะ ฉบับภาษาไทย ของฉุน ประภาวิวัฒน์; An Analytical Study of Siddharatha in Thai Version Translated by Chun Prapawiwat - ต้นโพธิ์ กาญจนา (Journal of Humanities and Social Sciences (HUSOKKU), 2017)
การศึกษาเชิงวิเคราะห์นวนิยายเรื่องสิทธารถะ ฉบับภาษาไทย ของฉุน ประภาวิวัฒน์ พบว่านวนิยายเรื่องนี้นำเสนอเนื้อหาเกี่ยวกับปรัชญาและหลักธรรมทางพระพุทธศาสนา โดยใช้กลวิธีการสร้างและจัดวางโครงเรื่องที่ลุ่มลึกและแยบคาย ซึ่งมีการจัดวางโครงเรื่องแบ่งเป็น 2 ภาค ภาคแรกมี 4 บท แฝงหลักธรรมที่เปรียบได้กับหลักอริยสัจ 4 และภาคที่ 2 มี 8 บท แฝงหลักธรรมที่เปรียบได้กับหลักอริยมรรค 8 และในด้านการใช้ภาษาแปลของฉุน ประภาวิวัฒน์ พบการใช้ภาษาสุภาพ การใช้คำโบราณ การซ้อนคำ การซ้ำคำ การใช้คำที่มีจังหวะและสัมผัสคล้องจอง การใช้คำแสดงภาพ และการใช้คำแสดงอาการ การใช้ภาษาแปลทั้งหมดของฉุน สะท้อนให้เห็นความสามารถในเชิงภาษาและการเลือกสรรถ้อยคำภาษาที่สละสลวยงดงาม แต่ในการแปลอาจมีการจัดแบ่งวรรคตอนใหม่หรือกล่าวไม่ตรงกับฉบับภาษาอังกฤษมากนัก โดยมักจะเพิ่มเติมคำหรือขยายความประโยคให้ยาวขึ้น เพื่อมุ่งนำเสนอภาษาสื่อจินตภาพที่ชัดเจนลึกซึ้งให้กับผู้อ่าน Abstract An Analytical Study of Siddharatha in Thai Version translated by Chun Prapawiwat indicated that the author presented the Buddhism philosophy and dharma through a delicate structure and a profound plot. The story was divided into two parts. The first part included 4 chapters comparable to the four greatest facts scriptures while the second part included 8 chapters comparable to the eight greatest paths scriptures. The findings from the language used in the translated version showed that Chun Prapawiwat, the translator, used the refined language and ancient words. Moreover, the reduplications and the synonymous compounds occurred in rhyme. In addition, the exquisite word choices, the subtle figurative language and the precise rhetorical devices used in the translation reflected the high capability of the translator. However, the translated version was moderately different from the original because the translator also rearranged the sentences and elaborated the phrases to illustrate clearer images to the audience.